High prevalence of pfmdr1 N86Y and Y184F mutations in Plasmodium falciparum isolates from Bioko island, Equatorial Guinea. (October 2014) - Li, Jian; Chen, Jiangtao; Xie, Dongde; Monte-Nguba, Santiago-m; Eyi, Juan Urbano Monsuy; Matesa, Rocio Apicante; Obono, Maximo Miko Ondo; Ehapo, Carlos Sala; Yang, Liye; Lu, Danjie; Yang, Hui; Yang, Hui-Tian; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: Drug resistance against Plasmodium falciparum has been recognized as the crucial obstacle to curbing mortality and morbidity from malaria. To investigate the distribution and pattern of multidrug resistance 1 (pfmdr1) gene polymorphisms in P. falciparum, isolates collected from the malaria high-endemic Bioko Island, Equatorial Guinea. Methods: Blood samples were collected from 217 patients with P. falciparum malaria during rainy season in 2012 on Bioko Island. These samples were extracted using Chelex to obtain parasite DNA. Nest-polymerase chain reaction (PCR) and sequencing were employed to detect mutations (N86Y, E130K, Y184F, S1034C, N1042D, V1109I, and D1246Y) and haplotypes in pfmdr1 gene. Results: A total of 151 samples were successfully detected for pfmdr1 mutations from the 217 patients. Pfmdr1 mutations were found in 91·39% (138/151) P. falciparum isolates. However, no mutation at 130 and 1109 was identified from these samples. Four haplotypes coding 86, 184, 1034, 1 042, and 1 246 were found including NYSND, YYSND, NFSND, and YFSND, which accounted for 8·61% (13/151), 2·65% (4/151), 29·80% (45/151), and 58·94% (89/151), respectively. Conclusions: Our results exhibited hypersensitivity to lumefantrine (LU) and mefloquine (MQ) and resistance to chloroquine (CQ) and amodiaquine (AQ) in P. falciparum isolates from Bioko Island. This information will be useful for anti-malarial drug policy in Equatorial Guinea.